Production And Testing Of Lateritic Interlocking Blocks - Raheem, Akeem Ayinde; Falola, Olugbenro Olusanjo; Adeyeye, Kehinde Joseph (Penerbit Universiti Sains Malaysia, 2012)
The production and testing of lateritic interlocking blocks were examined. The experiments involved the production of 250 × 130 × 220 mm3 interlocking blocks with laterite samples obtained from Aroje (Ogbomoso North L.G), Olomi (Ogbomoso South L.G), Idioro (Surulere L.G) and Tewure (Orire L.G) using a locally fabricated manual steel mould and a 4.5 kg rammer. The blocks were tested in the laboratory to determine their compressive strength, water absorption and resistance to abrasion. The results indicated that all of the stabilised blocks satisfied the minimum 28 day wet compressive strength of 1.0 Nmm–2 recommended by the Nigeria Building and Road Research Institute. The minimum seven day dry compressive strength for 5% cement stabilised blocks of not less than 1.60 Nmm–2, as recommended in the National Building Code, was not satisfied by all of the blocks. However, with 10% cement stabilisation, blocks from Olomi and Idioro laterites satisfied the minimum seven day strength with values of 2.13 Nmm–2 and 1.62 Nmm–2, respectively. Only laterites from Olomi and Idioro that met the minimum seven day requirements were concluded to be suitable for the production of interlocking blocks in southwestern Nigeria.